Priorities for service improvement in personality disorder in Australia: Perspectives of consumers, carers and clinicians. (8th June 2020) - Ng, Fiona; Townsend, Michelle L.; Jewell, Mahlie; Marceau, Ely M.; Grenyer, Brin F.S.
Abstract: Background: Improvements to service provision for personality disorder has been predominately explored through the perspectives of clinicians, with limited understanding of the views of consumers and carers. The aim of the present study was to understand the priorities for service improvement through multiple perspectives. Method: Twelve roundtables, with a total of 53 consumers, clinicians and carers, discussed how organizations could improve service provision for people with personality disorder and completed a questionnaire on current and optimal service provision. Inductive thematic analysis was used to identify the priorities for service improvement, and we aimed to identify differences between what participants currently receive and what they believe to be optimal. Results: Four priorities were identified: (1) increasing consumer, carer and peer involvement in care, (2) re‐orienting approaches to service provision, (3) improving access and accessibility of treatment and (4) building the capacity of services. Participants were more likely to receive individual or group treatment alone, yet believed combined individual and group treatment to be optimal. Significantly, more participants believed that long‐term treatment was optimal. Conclusion: A shift in focus from establishing a consistent approach to servicing, to focusing on holistic care that involves consumers and carers in care, is required. © 2020 The Authors Personality and Mental Health Published by John Wiley & Sons Ltd